Rewire your brain 2.0 : five healthy factors to a better life - Arden, John Boghosian (Tantor Media, Inc., 2023)
Not long ago, it was thought that the brain you were born with was the brain you would die with, and that the brain cells you had at birth were the most you would ever possess. Your brain was thought to be hardwired to function in predetermined ways. It turns out that's not true. Your brain is not hardwired; it's "softwired" by experience. This book shows you how you can rewire parts of the brain to feel more positive about your life, remain calm during stressful times, and improve your social relationships. Written by a leader in the field of Brain-Based Therapy, it teaches you how to activate the parts of your brain that have been underactivated and calm down those areas that have been hyperactivated, so that you feel positive about your life and remain calm during stressful times. You will also learn to improve your memory, boost your mood, have better relationships, and get a good night's sleep. Rewire Your Brain reveals how cutting-edge developments in neuroscience and evidence-based practices can be used to improve your everyday life. Explaining exciting new developments in neuroscience and their applications to daily living, this audiobook will guide you through the process of changing your brain so you can change your life and be free of self-imposed limitations